Endovascular Stenting for Malignant Obstruction of Superior Vena Cava: A Single-Center Experience Using the Body Floss Technique - Dayananda Lingegowda; Bharat Gupta; Anisha Gehani; Priya Ghosh; Sumit Mukhopadhyay (Journal of Clinical Interventional Radiology ISVIR)
Purpose Endovascular stenting is the treatment of choice for malignant obstruction of the superior vena cava (SVC) when rapid symptomatic relief is desired. Body floss technique is not routinely used during SVC stenting but has few advantages over single-access technique. We report our experience with stenting for malignant obstruction of the SVC using the body floss technique. Materials and Methods Between March 2015 and March 2020, 25 patients (20 men, 5 women; median age, 65 years) with malignant SVC obstruction underwent endovascular stenting of the SVC. We retrospectively evaluated these patients for clinical and technical success rates, complications, recurrence-free survival, and overall survival. Results Stent placement was successful in 24/25 patients (technical success: 96%). Clinical success was achieved in 23/25 (92%) patients. A mortality rate of 4% (1/25) was noted due to SVC rupture. Partial stent migration was noted in two patients (8%) and was treated by placing an additional overlapping stent. Incidental early stent thrombosis was seen in two patients within 8 hours of stent placement, but these patients showed symptom relief with anticoagulation. Follow-up imaging confirmed stent patency in all patients. Late stent occlusion due to tumor progression was seen in one patient. The primary patency rate was 88% (22/25). Overall median survival of 133 days was observed (range: 1–847 days). Conclusion Endovascular stenting of the SVC for malignant obstruction using the body floss technique is associated with high technical and clinical success, and low rate of complications.